Tri Nga and implementation of e-billing system intent to commit tax fraud - Wardani, Dewi Kusuma; Pawestri, Putri Dyah (Proceeding International Conference on Accounting and Finance, 2024)
This research aims to know the impact from lesson Tri Nga and the use of e-billing against objective for do shortage tax. Population taken was students of accounting Study Program student Bachelorwiyata Faculty of Economics Tamansiswa with sample used as many as 77 respondents. This study applies questionnaires as instrument inspection and resolution with take advantage of the SmartPLS program. Remember consequence from review this , got it explained that the use of e-billing affects in a way positive to intention carry it out tax fraud. Understanding about principle Tri- nga influential in a way negative to intention carry it out tax fraud